The impact of 8-week re-training following a 14-week period of training cessation on Greco-Roman Wrestlers - Burhan Demirkıran; Ali Işın; Yılmaz Sungur; Tuba Melekoğlu (PLoS ONE, 2025)
Background This study aimed to examine the changes in physical and physiological conditions in elite wrestlers from the Turkish National Wrestling Team, who experienced 14 weeks of restricted physical activity during the COVID-19 lockdown, followed by an 8-week period of retraining and competition. Methods Twenty male elite wrestlers from the National Greco-Roman Wrestling Team participated in the research. Heart Rate Variability values were measured during the training cessation period and for 8 weeks of subsequent training and then interpreted for training periods with different workloads. Body fat percentage values, initially measured during training cessation, were recorded at 2-week intervals during the training period. To determine the fitness status of wrestlers, the Specific Wrestling Fitness Test was used before and following the 8 weeks of training period. Results A gradual decrease in both body fat percentage and weight was observed throughout the course of the training period. The SWFT scores showed significant improvements (31.40 ± 2.91 vs. 37.40 ± 3.22) following the training period. Heart rate variability decreased during the detraining period, progressively improved throughout the 8-week retraining, and subsequently declined during the competition phase, reaching levels similar to those observed during training cessation. Conclusions Our results suggest that athletes undergo identical reactions in their autonomous nervous system during both competition and training cessation period. Obtaining a comprehensive understanding of these changes can enable coaches and athletes to make accurate decisions in order to optimize training adaptations and attain overall athletic success. Furthermore, over a period of eight weeks following a long non-training period, significant improvements in athletes’ body fat, muscle mass and wrestling performance can be achieved along with training. Moreover, HRV monitoring revealed that autonomic nervous system balance was compromised during both the 14-week detraining and the subsequent competition phases, underlining the need for careful training load management to optimize recovery and performance readiness.